Prediksi Volume Penyaluran Air Minum Kota Salatiga Tahun 2021 Berdasarkan Time Data Series Menggunakan Regresi Linear - Diva Christalivea; Magdalena A. Ineke Pakereng (Jurnal EMT KITA, 2023)
One of our most basic needs is water, water needed for the body and the need for cooking, washing, and other needs. Based on the number of customers, this study seeks to predict the volume of water that will be distributed. Valid data must be available for a long time to make accurate predictions. This is the benchmark for predicting patterns that are used to predict the next year, the data taken is a five-year timeframe, which is to predict the next year. A method used to predict, namely linear regression technique. A technique called linear regression is used to determine how close the relationship between the effect variable and the causal variable is. After forecasting, predictive data is generated in 2021, and compared to the previous year, there has been a change in the number of distribution volumes and customers. Where the total volume is predicted to be 4927284 and it is predicted that there will be 282126 customers in 2021.